Implementasi “Jari Sakti Dan Domino (JSD)” Dengan Platform Liveworksheet Untuk Meningkatkan Aktifitas Belajar Matematika Materi Trigonometri - Siti Fatimah (Balai Diklat Keagamaan Surabaya, 2022)
The purpose of this research is to increase student learning activities on special angles of trigonometry by implementing Jari Sakti dan Domino (JSD) with the Liveworksheet platform. The research on the implementation of Jari Sakti dan Domino (JSD) with the Liveworksheet platform on trigonometry special angles was carried out from April 2 to May 25 2022. The research subjects were class X MIPA 1 - 5 MAN I Mojokerto with a total of 175 students. The research instruments used were observation sheets and questionnaires. Observation of liveliness is carried out when learning takes place in the form of checklists. Observation sheet to get data on the level of student activity. The graphic results state that from the observation data it was found that the level of student learning activity reached 89.51% in the very good category and from the student questionnaire it was found that students felt very happy learning by applying Jari Sakti dan Domino (JSD) reaching 93.14%, very able to apply Jari Sakti dan Domino (JSD) reached 91.43%, easy to practice 90.29% and could say the value of the special angle in quadrants I - IV reached 90.86%. This research has been able to improve the mathematics learning activities of class X MIPA students at MAN I Mojokerto in trigonometry by implementing